Social network mining, analysis, and research trends techniques and applications - Ting, I-Hsien.; Hong, Tzung-Pei, 1963-; Wang, Leon Shyue-Liang, 1955- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book covers current research trends in the area of social networks analysis and mining, sharing research from experts in the social network analysis and mining communities, as well as practitioners from social science, business, and computer science"--Provided by publisher.